A Present Absence: Reading Redaction Poetry - Zuliani, Andy (FRAME, Journal of Literary Studies, 2026)
This article is an examination of an emergent form of contemporary literature, referred to here as ‘redaction poetry.’ This poetic practice, an extension of earlier modes of ‘erasure’ poetry, undertakes a radical effacement of existing texts—often drawn from non-literary, and especially governmental, contexts—in order to carve out of this substrate its own, highly subversive meanings. As a result of this highly visual and often material practice, redaction poetry is uniquely poised between competing media and genres. This article argues that while this blurring of boundaries might make these works unstable, and difficult to categorize and preserve, it also renders them uniquely able to invade and disrupt the textual and media economies of the present.